L’usage du principe de proximité comme instrument d’ajustement de la décision publique - Christian Nicourt; Jean Max Girault (Développement Durable et Territoires)
The assumption of this article is that plastic and polysemous dimensions allotted by actors to the concept of proximity makes it as a government instrument as much as a spring of mobilization legitimating the oppositions. It is tested in the context of conflicted public legal inquieries concerning platforms of mud composting in french Dordogne. The analysis highlights the confrontation of two conceptions of proximity. In one hand, it is a territory of activities and collective experiments. In the other hand, social dimension has been eroded to provide a management parameter. The expression of these legitimacies underlines the room to manœuvre with the principle of proximity and clearly reveals the dissymmetric power of its users.